Occurrence of Proteus mirabilis associated with two species of venezuelan oysters Ocorrência de Proteus mirabilis associado a duas espécies de ostras venezuelanas - Milagro Fernández-Delgado; Monica Contreras; María Alexandra García-Amado; Pulchérie Gueneau; Paula Suárez (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
The fecal contamination of raw seafood by indicators and opportunistic pathogenic microorganisms represents a public health concern. The objective of this study was to investigate the presence of enteric bacteria colonizing oysters collected from a Venezuelan touristic area. Oyster samples were collected at the northwestern coast of Venezuela and local salinity, pH, temperature, and dissolved oxygen of seawater were recorded. Total and fecal coliforms were measured for the assessment of the microbiological quality of water and oysters, using the Multiple Tube Fermentation technique. Analyses were made using cultures and 16S rRNA gene sequencing. Diverse enrichment and selective culture methods were used to isolate enteric bacteria. We obtained pure cultures of Gram-negative straight rods with fimbriae from Isognomon alatus and Crassostrea rhizophorae. Our results show that P. mirabilis was predominant under our culture conditions. We confirmed the identity of the cultures by biochemical tests, 16S rRNA gene sequencing, and data analysis. Other enterobacteria such as Escherichia coli, Morganella morganii and Klebsiella pneumoniae were also isolated from seawater and oysters. The presence of pathogenic bacteria in oysters could have serious epidemiological implications and a potential human health risk associated with consumption of raw seafood. A contaminação fecal de frutos do mar crus por microrganismos oportunistas patogênicos representa problema de saúde pública. O objetivo deste estudo é investigar a presença de bactérias entéricas que colonizam ostras coletadas em área turística da Venezuela. Amostras de ostras foram coletadas na costa noroeste da Venezuela e foram registrados a salinidade local, pH, temperatura e o oxigênio dissolvido na água do mar. O total de coliformes fecais foi medido para a avaliação da qualidade microbiológica da água e das ostras, usando a técnica de fermentação em tubos múltiplos. Análises foram feitas usando culturas e seqüência do gene 16S rRNA. Enriquecimento diversificado e métodos de cultura seletivos foram usados para isolar a bactéria entérica. Obtivemos culturas puras de bastões retos Gram negativos com fímbrias de Isognomon alatus e Crassostrea rhizophorae. Nossos resultados mostram que P. mirabilis foi predominante nas nossas condições de cultura. Confirmamos a identidade das culturas por testes bioquímicos, seqüência do gene 16rRNA e a análise de dados. Outras enterobactérias como Escherichia coli, Morganella morganii e Klebsiella pneumoniae foram também isoladas da água do mar e ostras. A presença de bactérias patogênicas em ostras podem ter implicações epidemiológicas e potencial risco para a saúde humana quando do consumo de frutos do mar crus.